Comparison of Serum Adipocytokine Levels according to Metabolic Health and Obesity Status - Lee, Tae Hoon (Endocrinol Metab (Seoul), 2015)
BACKGROUND: Metabolic health is an emerging concept that is highly correlated with various metabolic complications, and adipocytokines have been causally linked to a wide range of metabolic diseases. Thus, this study compared serum adipocytokine levels according to metabolic health and obesity status. METHODS: Four hundred and fifty-six nondiabetic subjects (mean age, 40.5 years) were categorized into four groups according to metabolic health and obesity status: metabolically healthy nonobese (MHNO), metabolically healthy obese (MHO), metabolically unhealthy nonobese (MUHNO), and metabolically unhealthy obese (MUHO). Being metabolically healthy was defined as the presence of fewer than two of the following five metabolic abnormalities: high blood pressure, high fasting blood glucose, high triglyceride, low high density lipoprotein cholesterol, and being in the highest decile of the homeostatic model assessment of insulin resistance index. Obesity status was assessed using body mass index (BMI), with obesity defined as a BMI higher than 25 kg/m(2). Levels of serum interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor α (TNF-α), and adipocyte fatty acid binding protein (A-FABP) were also evaluated. RESULTS: Of the 456 subjects, 247 (54.2%) were in the MHNO group, 66 (14.5%) were in the MHO group, 66 (14.5%) were in the MUHNO group, and 77 (16.9%) were in the MUHO group. There were no significant differences in IL-6 or MCP-1 levels among the groups, but levels of TNF-α and A-FABP were significantly higher in the MUHNO group compared to the MHNO group. CONCLUSION: High TNF-α and A-FABP levels are significantly associated with metabolically unhealthiness in nonobese Korean individuals.